Strategies for the Synthesis of Heterocycles and Their Applications - Kumari, Premlata; Patel, Amit B. (IntechOpen, 2023)
Heterocycles are present in the molecular architecture of a wide variety of natural products and compounds with significant biological potency. The numerous heterocycles are employed as significant intermediates in the fields of synthetic organic chemistry, pharmaceuticals, and organic synthesis. This book summarizes the synthesis of different heterocycles using various synthetic methods, including green methods, and applications of heterocycles in various fields.